The outcome of Acute Kidney Injury in patients with severe Malaria - Brandão, João Alberto; Jr., oão Egidio Romão (Journal of Clinical Nephrology, 2017)
Background: Acute kidney injury (AKI) is a frequent and serious clinical complication in patients with severe malaria. The purpose of this study was to assess the incidence of AKI in a large population of hospitalized patients with a primary admission diagnosis of malaria, and to investigate the robustness of the KDIGO criteria for predicting the need for dialysis, length of hospital stay and hospital mortality. Results: We studied 695 consecutive patients admitted with primary diagnoses of malaria, in a 6 months period. AKI occurred in 86 (12.4%) patients (Stage 1 in 30.2%, Stage 2 in 23.3% and Stage 3 in 46.5%), and 19 (22.1%) patients required hemodialysis. No patient in the no-AKI or AKI Stage 1 groups (admission or maximum AKI Stage) required hemodialysis, and the requirement of hemodialysis was higher in patients with AKI Stage 2 (23.1%) and Stage 3 (42.4%). The length of hospital stay was longer (7.3±7.4 days vs 5.1±3.0 days; t=4.996, p<0.0001), and mortality was higher in patients who developed AKI than in those who did not (22,5% vs 2,5%; χ2=79.52; p<0.0001). Patients with AKI Stage 1, 2 and 3 had significantly higher hospital mortality (11%, 23% and 30%, respectively), compared with 2.5% for patients without AKI [odds ratio 5.2 (1.40-19.11, p=0.0331), 13.2 (4.24-41.06, p=0.0002), and 16.9 (7.26-36.65, p<0.0001)], respectively. Conclusion: In a relatively large cohort of patients with falciparum malaria infection, the KDIGO criteria identified 12.4% with a diagnosis of AKI. The KDIGO classification was robust in this population for predicting the need for dialysis, length of hospital stay and hospital mortality. The results support the utilization of the KDIGO criteria in diagnosis and to predicting outcomes for patients with malarial AKI.